Waste management of pseudostem to increase the growth of banana seedlings - Lima, Juliana Domingues [UNESP]; de Souza Bravo, Natália [UNESP]; Rozane, Danilo Eduardo [UNESP]; Nomura, Edson Shigueaki; da Silva, Silvia Helena Modenese Gorla [UNESP]; Gomes, Eduardo Nardini [UNESP] (Universidad Nacional de Colombia, 2020)
Pseudostem is an abundant residue after harvesting of the banana bunch, serving as a source of water, nutrients and organic substances. The present study aimed to evaluate the effect of pseudostem waste on 'Nanica' banana (Musa spp. AAA) cultivar in greenhouse under contrasting environmental conditions. For this, an experiment was carried out in in the São Paulo State University -UNESP in a randomized block design in a 2 x 2 factorial scheme (presence or absence of waste and two seasons), consisting of four replicates of three experimental plots with two pots per plant. One season was early November/2018 (Summer) and the other half of May/2019 (Winter). A 40 cm portion of the pseudostem collected from of a freshly harvested plant was sectioned into 10 cm portions and placed under the substrate of the seedling-containing pot at both times. Periodically, height, pseudostem diameter and leaf emission were evaluated. After the release of leachate by the residue, plants were taken to the laboratory, and the area of leaves and roots, their respective masses, and the leaf nutrient content were determined. The nutritional composition of the residue was evaluated before being applied for both seasons. In summer, accumulated dry matter in the different organs, leaf area and root area was higher in the presence of the residue, while in winter, only root dry mass was higher (P < 0.01). The application of residue had a consistent effect on root growth, which can be exploited in the field.
Keywords: Growth promoting substances; Nutrient cycling; Vegetables residues